The development of intonation in the oral expression of the english language - Olaya Moran, Cinthia Lili; Mesa Uzhea, Irvin Mauricio (Machala, Utmachala, 2023)
The purpose of this work is to improve the intonation in the oral expression of the English language in the students of the first parallel baccalaureate "B" of the Carmen Mora de Encalada school through implementing a didactic strategy based on the use of playful methods that contribute to the positive development of intonation through dynamic games that contribute to the meaningful learning of students. Educational research is developed subject to a qualitative methodological paradigm, with a participatory action-research design, considering the use of empirical and theoretical level methods, as well as sustainable techniques to measure the scope of this work. Based on all the needs of the students and being able to implement optimal knowledge through the real and flexible practice of each student.
El presente trabajo tiene como finalidad el mejoramiento de la entonación en la expresión oral del idioma inglés en los estudiantes de primero bachillerato paralelo “B” del colegio Carmen Mora de Encalada a través de implementar una estrategia didáctica sustentada en el empleo de métodos lúdicos que contribuyan al desarrollo positivo de la entonación mediante dinámicos juegos que contribuyen al aprendizaje significativo de los estudiantes. Se desarrolla una investigación educativa sujeta a un paradigma metodológico cualitativo, con un diseño de tipo investigación-acción participativa, se considera el uso de los métodos del nivel empírico y nivel teórico también técnicas sustentables para medir el alcance del presente trabajo. En base a todas las necesidades de los estudiantes y pudiendo implementar un conocimiento optimo mediante la practica real y flexible de cada alumno.
Keywords: DESARROLLO; APRENDIZAJE; ESTUDIANTE; METODO